2010
DOI: 10.1292/jvms.10-0124
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Genes and Antimicrobial Susceptibilities of Hemolytic and Nonhemolytic Escherichia coli Isolated from Post-Weaning Piglets in Central Thailand

Abstract: ABSTRACT. The purpose of this study was to compare the existence of virulence genes in hemolytic Escherichia coli (HEC) and nonhemolytic E. coli (NHEC) isolated from weaner pigs in Thailand, and to determine their susceptibility to 10 antimicrobial agents. A total of 304 E. coli isolates were obtained from 90 piglets with diarrhea and 110 healthy piglets. Of these, 74 HEC isolates were obtained from 70 pigs with diarrhea, and 4 were obtained from 4 healthy pigs, while 190 and 40 NHEC were recovered from 110 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
3
14
1
Order By: Relevance
“…In three publications, AMR was investigated in both E. coli and NTS isolates. The majority of publications included data from Thailand (20) [27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44] and Vietnam (15) [18,23,45,46,47,48,49,50,51,52,53,54,55]. One publication was found with data from each of Cambodia, Indonesia, Lao PDR and Malaysia [56,57,58,59].…”
Section: Resultsmentioning
confidence: 99%
“…In three publications, AMR was investigated in both E. coli and NTS isolates. The majority of publications included data from Thailand (20) [27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44] and Vietnam (15) [18,23,45,46,47,48,49,50,51,52,53,54,55]. One publication was found with data from each of Cambodia, Indonesia, Lao PDR and Malaysia [56,57,58,59].…”
Section: Resultsmentioning
confidence: 99%
“…Thai isolates tested here showed higher resistance to ERFX with MIC values of 3.2-25 μg/ml, and in addition, the rate of ERFX resistant isolates was also higher than those reported in the previous papers. This may reflect the overuse of ERFX in pig farming in Thailand, especially for treatment of diarrhea of lactating piglets and at nursery up to 9 weeks [15]. Since the mechanisms of resistance to ERFX of Thai isolates were not examined in the present study, a further study is needed to elucidate whether the resistance to ERFX of Thai isolates comes from alteration of the genes coding for DNA gyrase or reduction of quinolone accumulation by active efflux [8].…”
mentioning
confidence: 95%
“…Management practices, medication and vaccination are control measures of the disease [12]. In Thailand, antimicrobials are generally given to piglets to control diarrhea and respiratory problems during weaning to fattening as well as to gilt and sow during gilt acclimatization and lactation [15]. Excessive medication may cause a decrease of susceptibility of mycoplasmas against antimicrobial agents [11,21,23].…”
mentioning
confidence: 99%
“…However, a larger sample size would be needed in any future studies to estimate the true prevalence rates of pathogenic E. coli among the Malaysian swine populations. A recent study from Thailand [15] reported a relatively higher prevalence of VTEC (11.2%) from pigs with PWD. The results obtained in this study and that of Prapasarakul et al [15] were in contrast with earlier reports by Zhang et al [16] and Fairbrother et al .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Thailand [15] reported a relatively higher prevalence of VTEC (11.2%) from pigs with PWD. The results obtained in this study and that of Prapasarakul et al [15] were in contrast with earlier reports by Zhang et al [16] and Fairbrother et al . [2] who reported ETEC as the most common pathotype found in pigs with PWD in the United States and worldwide, respectively.…”
Section: Discussionmentioning
confidence: 99%